Respuesta :
Answer:
-160x³
Step-by-step explanation:
4th term: n = terms - 1 = 4-1 = 3
1*1⁶*(-2x)⁰ + 6*1⁵*(-2x)¹ + 15*1⁴*(-2x)² +20*1³*(-2x)³ + 15*1²*(-2x)⁴ + ..........
↑
4th term
20*1³*(-2x)³ = 20*(-8x³) = -160x³
The fourth term of the expansion of (1 - 2x)ⁿ is; A; -160x³
Binomial Expansion Theorem
We want to find the fourth term of the expansion given as;
(1 - 2x)ⁿ
Using binomial coefficients, the first 7 coefficients are;
1 6 15 20 15 6 1
Now, using the binomial expansion method, we have;
(1 - 2x)⁶ = (1 × 1⁶ × (-2x)⁰) + (6 ×1⁵ × (-2x)¹) + (15 × 1⁴ × (-2x)²) + (20 × 1³ × (-2x)³) + (15 × 1² × (-2x)⁴) + .......
Looking at the expansion, the fourth term is identified as; (20 × 1³ × (-2x)³)
Simplifying that gives; -160x³
Read more about Binomial Expansion at; https://brainly.com/question/13602562